Early skeletal muscle loss and clinical outcomes in critically ill patients in the medical intensive care unit: A retrospective cohort study - Soyun Kim; Da Hyun Kang; Dukki Kim; Soyoung Ahn; Mi Ra Lee; Song I Lee (PLoS ONE, 2025)
Background Acute skeletal muscle wasting is a common complication among critically ill patients and contributes to prolonged stays in the intensive care unit (ICU) and poor outcomes. Although bedside ultrasound of the rectus femoris cross-sectional area (RFcsa) is useful for assessing muscle loss, data on its incidence and predictors in medical ICU populations are limited. Our study aimed to determine the incidence of significant muscle wasting (≥10% reduction in RFcsa) and to identify modifiable predictors, particularly early rehabilitation. Methods This retrospective cohort study was conducted at a tertiary academic hospital in South Korea. Seventy-six adult ICU patients who underwent serial ultrasound assessments of RFcsa within 48 h of admission and again on day 7 were included. Patients were categorized based on whether they experienced a ≥ 10% reduction in RFcsa. Clinical characteristics, interventions, and outcomes were compared between groups. Multivariate logistic regression identified predictors of significant muscle loss, ICU mortality, and in-hospital mortality. Results A significant reduction in RFcsa (≥10%) was observed in 53.9% of patients (n = 41/76). These patients had longer ICU stays (median 15.0 vs. 10.0 d, p = 0.001) and were less likely to receive Level 3 or higher ICU-level rehabilitation (4.9% vs. 20.0%, p = 0.042). Multivariate analysis revealed that Level 3 or higher rehabilitation was independently associated with reduced muscle wasting (OR: 0.183; 95% CI: 0.035–0.970; p = 0.046). Multivariable analyses revealed that increased total bilirubin and decreased albumin levels were associated with ICU mortality. In-hospital mortality, however, was independently associated with a higher Charlson comorbidity index, elevated bilirubin and C-reactive protein levels, and low albumin. A decrease in RFcsa of at least 10% was not significantly associated with either outcome. Conclusions More than half of the patients in the ICU experienced significant muscle loss within the first week of being admitted. Receiving structured rehabilitation at Level 3 or higher was independently associated with reduced muscle wasting. This suggests that early mobilization strategies may help preserve muscle mass in critically ill patients.